Resilience indicators for measuring sustainable economic development - Burlutskyi, Serhii; Burlutska, Svitlana; Marhasova, Viktoriia (My University, 2017)
Ціль статті полягає в тому, щоб розглянути питання про дослідження послідовних структур стійкого розвиток соціально-економічних систем. Теоретичне пояснення цієї гіпотези має емпіричне обґрунтування перевірка шляхом дослідження поведінки соціально-економічної системи України. Аналіз результати систем диференціальних рівнянь (аналог рівнянь Лотки-Вольтера) і перетворення фазового простору в тимчасовому режимі указують на можливість існування періодичних коливань обсягів виробництва, засобів виробництва (товар Х) і споживання товару (товар Y). У статті пропонується визначити показники пружності для виміру пружного економічний розвиток. Перевіряється "екологічна" концепція пружності залежно від рівня відтворення після шокового впливу. The aim of this paper is to address to research the consistent patterns of the sustainable development of socio-economic systems. Theoretical explanation of this hypothesis has empirical verification by means of the research of the socio-economic system behavior of Ukraine. The analysis results of the systems of differential equations (the analogue the Lotka–Volterra equations) and the transformation of the phase space in the temporal mode for individual products indicate the possibility of existence of periodic fluctuations of output, means of production (commodity X) and consumption goods (commodity Y). The paper proposes to identify the resilience indicators for measuring sustainable economic development. Methodical recommendations on forecasting of changes trends in the "ecological" concept of resilience are tested focusing on depending on the level of the index postshock recovery.
Keywords: експортна детермінанта; соціально-економічна стійкість; концентрація; диверсифікованість; структурні зрушення; export determinant; socio-economic resilience; concentration; diversification; structural shifts; кафедра економіки праці та менеджменту